PENGARUH PROMOSI DAN DISTRIBUSI TERHADAP MINAT DAYA BELI DENGAN CITRA MEREK PADA UD KERIPIK TEMPE MATAHARI DHARMASRAYA - Endi Rustendi, Endi (Manageable, 2025)
This community service activity takes place in the desa tiumang,kecamatan sitiung,kabupaten dharmasraya. The main purpose of this PKM is for development of Desa Tahunan to increase PAD (Pendapatan Asli Daerah) pursued from various aspects of the program, including the development of tempe production into processed products in the form of tempe chips. Keripik Tempe Desa Tahunan have good image and quality of chips, but business management is still simple, has no business identity and product labels/packaging. Some of the problems include lack of partner human resources capabilities in terms of marketing, making financial statements, and still lacking product innovation. The method used in this community service activity is online- based marketing training, financial management for SMECs, packaging and labeling and photography techniques for tempe chips. In addition to the training programs are also carried out with the installation of business identity/banner, design and printing of product labels and packaging. The team also carried out mentoring activities with the aim of ensuring the activities were in accordance with the objectives of the implementation. The results obtained from the community service activities include increasing the ability of partners in optimizing online-based marketing media, having a product label, having a business identity, and improving the ability to do photography to produce good images to be displayed in marketing media.